Estudio limnológico en el lago Pellegrini (Río Negro, Argentina) - Conzonno, Víctor H.; Mariazzi, Aldo A.; Casco, María A.; Echenique, Ricardo; Labollita, Héctor A.; Petrocchi, Margarita (Ecosur, 2024)
Results of an investigation on nutrients, primary production, chlorophyll and phytoplankton in Pellegrini Lake (hard waters artificial ecosystem) are presented. The hardness was around 350 mg CO3Ca per liter, total phosphorus, total inorganic nitrogen and reactive silica showed very low values. The contribution of algae fraction below 25 μm to total primary production and clorophyll was very high. Phytoplankton was represented by 70 taxa and four were dominant in diferent periods: Oocystis parva Chlorococcales (not identified), Marismopedia tenuissima and Chaetoceros sp. Some considerations are made about calcium and macrophytes influence on nutrients levels, primary production and phytoplankton composition.